Resting-state functional connectivity alteration in elderly patients with knee osteoarthritis and declined cognition: An observational study - Lin, Guanwen; Lan, Fei; Wu, Duozhi; Cao, Guanglei; Li, Zheng; Qi, Zhigang; Liu, Yang; Yang, Shuyi; Lu, Jie; Wang, Tianlong (Frontiers in Aging Neuroscience, 2022)
Objective: This study is designed to investigate the brain function changed regions in elderly patients with knee osteoarthritis (KOA), and exploring the relationship between neuropsychological tests and resting-state functional magnetic resonance imaging (rs-fMRI) network in order to clarify the possible mechanism underlying cognitive changes in KOA patients. Methods: Fifty-two patients aged ≥65 with KOA and twenty-two healthy matched controls were recruited in this study. All participants were given rs-fMRI check. We used graph theory analysis to characterize functional connectivity (FC) and topological organization of the brain structural network. The relationship between FC values, topological properties and the neuropsychological test scores was analyzed. Results: Compared with the controls, fourteen edges with lower functional connectivity were noted in the KOA group. Local efficiency and small-worldness of KOA patients decreased compared to the healthy controls. No significant alterations of nodal topological properties were found between two groups. There was a significant positive correlation between the AVLT-H (L) and the internetwork of default mode network (DMN) (left/right orbitofrontal Superior cortex) and Limbic/cortical areas (left/right caudate, right amygdala). AVLT-H(L) was positively correlated with small-worldness and local efficiency. Conclusion: The results indicated that compared to healthy controls, topological properties, FC between DMN and subcortical limbic network related regions in elderly patients with KOA and declined cognition significantly decreased. These alterations demonstrated significant correlation with the neuropsychological test scores.